Cancer statistics for adolescents and young adults, 2020. (17th September 2020) - Miller, Kimberly D.; Fidler‐Benaoudia, Miranda; Keegan, Theresa H.; Hipp, Heather S.; Jemal, Ahmedin; Siegel, Rebecca L.
Abstract: Cancer statistics for adolescents and young adults (AYAs) (aged 15‐39 years) are often presented in aggregate, masking important heterogeneity. The authors analyzed population‐based cancer incidence and mortality for AYAs in the United States by age group (ages 15‐19, 20‐29, and 30‐39 years), sex, and race/ethnicity. In 2020, there will be approximately 89, 500 new cancer cases and 9270 cancer deaths in AYAs. Overall cancer incidence increased in all AYA age groups during the most recent decade (2007‐2016), largely driven by thyroid cancer, which rose by approximately 3% annually among those aged 20 to 39 years and 4% among those aged 15 to 19 years. Incidence also increased in most age groups for several cancers linked to obesity, including kidney (3% annually across all age groups), uterine corpus (3% in the group aged 20‐39 years), and colorectum (0.9%‐1.5% in the group aged 20‐39 years). Rates declined dramatically for melanoma in the group aged 15 to 29 years (4%‐6% annually) but remained stable among those aged 30 to 39 years. Overall cancer mortality declined during 2008 through 2017 by 1% annually across age and sex groups, except for women aged 30 to 39 years, among whom rates were stable because of a flattening of declines in female breast cancer. Rates increased for cancers of the colorectum and uterine corpus in the group aged 30 to 39 years, mirroring incidence trends. Five‐year relative survival in AYAs is similar across age groups for all cancers combined (range, 83%‐86%) but varies widely for some cancers, such as acute lymphocytic leukemia (74% in the group aged 15‐19 years vs 51% in the group aged 30‐39 years) and brain tumors (77% vs 66%), reflecting differences in histologic subtype distribution and treatment. Progress in reducing cancer morbidity and mortality among AYAs could be addressed through more equitable access to health care, increasing clinical trial enrollment, expanding research, and greater alertness among clinicians and patients for early symptoms and signs of cancer. Further progress could be accelerated with increased disaggregation by age in research on surveillance, etiology, basic biology, and survivorship.